A green economy in major regional cities of Poland – the status of its implementation and transformations in the public sector - Plac, Klaudia (Zielona gospodarka w miastach wojewódzkich Polski – stan wdrażania oraz przekształcenia w sektorze publicznym, 2019)
The aim of the article is to compare the status of implementing a green economy in selected aspects of management (transport, municipal engineering and environmental protection) in the system of Poland’s regional cities, as well as the assessment of cities’ similarity in the studied area and the dynamics of the process of adaptation to the requirements of a green economy The study has included Poland’s 18 regional cities, i.e. Białystok, Bydgoszcz, Gdańsk, Gorzów Wielkopolski, Katowice, Kielce, Kraków, Lublin, Łódź, Olsztyn, Opole, Poznań, Rzeszów, Szczecin, Toruń, Warszawa, Wrocław and Zielona Góra. Its time scope covered the period 2012-2017. The collected data were used to develop 58 quantitative indicators regarding two aspects: transport and municipal engineering, as well as environment protection in cities, which were later used to analyse the similarity (grouping) of the studied cities with agglomerative methods
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 2, s. 81-90
Keywords: green economy; comparative analysis of cities; regional cities; Poland; zielona gospodarka; analiza porównawcza miast; miasta wojewódzkie; Polska